Isolation of Corynebacterium pseudotuberculosis Biovar equi from a Horse in Central Iowa - Kate L. Hepworth-Warren; Beatrice T. Sponseller; David M. Wong; Joann M. Kinyon (Case Reports in Veterinary Medicine)
Corynebacterium pseudotuberculosis biovar equi is the causative agent of “pigeon fever,” or “dryland distemper” in horses. The agent is typically identified in the Western United States but has recently been identified in Canada; it has not previously been documented as cause of infection in horses in Iowa. This report describes the clinical findings of two horses in Iowa that presented with pectoral abscessation, confirmed in one to be C. pseudotuberculosis biovar equi.